THE LANGUAGE OF THE BETUNGKAL CEREMONY: AN ECOLOGICAL APPROACH - Garner, Mark; Supardi, Iwan (Kajian Linguistik dan Sastra, 2008)
The discourse of ritual may be one of the clearest and most fundamental mani- festations of language in its ecological setting. It simultaneously manifests and re- creates the three dynamic systems of socialityâcommunication, culture, and com- munity. In this paper we examine the language in betungkal, a traditional anoint- ing ceremony of West Kalimantan. The language is characterized by complex pat- terning, showing by both constant repetition and variation, and thus demonstrates the fundamental processes of predictability and creativity by which every form of linguistic communication operates. It is a paradigmatic example of how language is taught and reinforced, from discourse as embedded in the environment, to a communityâs members of whatever age. At the same time it inevitably teaches and reinforces the communityâs identity and its cultural values and practices.Â Key words: ecological approach, anointing, ritual art, and betungkal.Â